ANALISIS PERHITUNGAN SALDO DAN PROSEDUR KLAIM JAMINAN HARI TUA PADA BPJS KETENAGAKERJAAN KCP SANGATTA - Adinda Charoline Sabatini; Saiful; Rosmiati Pakata (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
The purpose of this study was to find out how to calculate the old-age security balance and describe the implementation of online and offline old-age insurance claim procedures at BPJS Printis Branch Office (KCP) Sangatta. Data collection methods were obtained from BPJS Ketenagakerjaan KCP Sangatta documents, interviews and the formula for calculating the Old Age Security (JHT) balance, which then analyzed the data so that conclusions could be drawn. Proving that the implementation of the Old Age Security (JHT) claim procedure at BPJS Ketenagakerjaan KCP Sangatta is in accordance with existing regulations, but there are still many registered participants who have not yet entered retirement age, have already claimed Old Age Security (JHT) due to lack of information.